2013
DOI: 10.1093/eurjhf/hfs165
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of undetected heart failure in long‐term care residents: findings from the Heart Failure in Care Homes (HFinCH) study

Abstract: AimsDiagnosis of heart failure in older people in long-term care is challenging because of co-morbidities, cognitive deficit, polypharmacy, immobility, and poor access to services. This study aimed to ascertain heart failure prevalence and clinical management in this population.Methods and resultsA total of 405 residents, aged 65–100 years, in 33 UK care facilities were prospectively enrolled between April 2009 and June 2010. The presence of heart failure was determined using European Society of Cardiology gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 37 publications
5
45
2
1
Order By: Relevance
“…Hancock et al found a prevalence of AHF in almost a quarter of older residents in long-term care facilities, while Oudejans et al reported a prevalence of 46% in older patients admitted to hospital with HF symptoms. 1,27 The mean age and gender distributions of patients of these studies were comparable to those of our study population. As in our study, the final diagnosis of AHF was adjudicated in those studies by two specialists independently reviewing echocardiography, ECG, and physical findings indicating high quality of analysis.…”
Section: Acute Heart Failure In the Elderlysupporting
confidence: 75%
See 1 more Smart Citation
“…Hancock et al found a prevalence of AHF in almost a quarter of older residents in long-term care facilities, while Oudejans et al reported a prevalence of 46% in older patients admitted to hospital with HF symptoms. 1,27 The mean age and gender distributions of patients of these studies were comparable to those of our study population. As in our study, the final diagnosis of AHF was adjudicated in those studies by two specialists independently reviewing echocardiography, ECG, and physical findings indicating high quality of analysis.…”
Section: Acute Heart Failure In the Elderlysupporting
confidence: 75%
“…Of note, the Heart Failure in Care Homes (HFinCH) Diagnostic Accuracy Study suggested that up to half of older HF patients were undiagnosed, while three-quarters of patients previously diagnosed with HF had been misclassified. 1 Symptoms and signs might be substantially less clear in older patients compared to younger individuals, and they may be more difficult to detect due to the presence of one or several comorbid conditions. 27 …”
Section: Acute Heart Failure In the Elderlymentioning
confidence: 99%
“…The reported prevalence of HF in nursing homes ranges from 20.0 to 37.4 %. 7 The Heart Failure in Care Homes (HFinCH) study 8 found a higher prevalence of HF in UK care-facility residents aged 65-100 years than in community populations. Most cases were previously undiagnosed and three-quarters of previously recorded cases were unconfirmed using the latest European Society of Cardiology (ESC) guidelines, echocardiogram and brain natriuretic peptide measurements.…”
Section: Care Planning In Skilled Nursing Facilitiesmentioning
confidence: 99%
“…The precise prevalence of HF among SNF residents is unknown, with estimates ranging between 20% and 37.4%. 2,[16][17][18][19] Of the estimated 1 492 200 Americans (nearly 0.5% of the total US population) living as long-term residents in SNFs, 3 1 317 200 (nearly 90%) were ≥65 years of age, representing nearly 5% of the population aged ≥65 years. More than 70% of these were women, and nearly half were ≥85 years old.…”
Section: Epidemiology Of Hf In Snfsmentioning
confidence: 99%